Effect of Al₂O₃, RHF, and RHA on gamma shielding and mechanical properties of TeO₂-Based glass using Phy-X/PSD - Floressy Juhim; Fuei, Pien Chee; Asmahani Awang; Saafie Salleh; Muhammad Izzuddin Rumaling; Amani Alalawi; M.S. Al-Buriahi (Elsevier Ltd., 2025)
Radiation attenuation behaviour of TeO₂–ZnO–Bi₂O₃–Na₂O–Er₂O₃ with the addition of Al₂O₃ nanoparticles (NP), rice husk fibre (RHF), and rice husk ash (RHA) was investigated using Phy-X/PSD software. The mass attenuation coefficients of the chosen glasses were measured from 0.015 to 3 MeV. The results showed that increasing the RHF concentration of the glasses or decreasing the Al₂O₃ component of the glass system enhances the mass attenuation coefficient of the material. At low energy, there is a significant difference between the mass attenuation coefficients values of the samples with the lowest and highest Al₂O₃ content, where the difference is 0.05118 cm2/g at 0.015 MeV. TZNERHF had higher mass attenuation coefficients (0.05402 cm2/g), and TZNETiAl8 had the highest mass attenuation coefficients, with a value of 0.05357 cm2/g at 1.173 MeV. The results showed a decreasing trend in the half-value layer (HVL), tenth value layer (TVL), and mean free path (MFP) when the density increased from 5.12555 to 5.23882 g/cm3 and attenuation ability improved. Subsequently, the influence of Al₂O₃ on Zeff values became more considerable as Zeff values increased. The shielding qualities of their glass samples are also superior to commercial window glass and common shielding concrete. Thus, the glass samples can be used with excellent advantage as radiation shielding materials. The findings showed that adding RHF and lower Al₂O₃ enhanced the studied samples' radiation shielding properties. The results show that the TZNERHF glass sample has the highest mechanical properties. Thus, the TZNERHF sample is better than the other glass samples.